2012
DOI: 10.4314/ajpsy.v15i2.15
|View full text |Cite
|
Sign up to set email alerts
|

Short-term diagnostic stability among re-admitted psychiatric in-patients in Eldoret, Kenya

Abstract: Objective: To determine the prospective and retrospective consistency of diagnoses among readmitted psychiatric in-patients at the Moi Teaching and Referral Hospital in Eldoret, Kenya. Method: Admission and discharge diagnoses among a consecutive sample of 114 psychiatric in-patients readmitted at the Moi Teaching and Referral Hospital between August and December 2009 were compared. Results:The commonest diagnoses at admission were schizophrenia spectrum disorders (47.4%) and bipolar spectrum disorders (30.7%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 28 publications
0
5
0
2
Order By: Relevance
“…We also found that most patients retained the diagnosis of schizophrenia in the four years after its onset (65%). Although schizophrenia has a high diagnostic stability, according to previous works, prospective consistencies can vary from 52–100% 4549 . In our sample approximately 35% of the patients diagnosed with schizophrenia, presented a change in their diagnosis (prospective consistency of 65%).…”
Section: Discussionmentioning
confidence: 99%
“…We also found that most patients retained the diagnosis of schizophrenia in the four years after its onset (65%). Although schizophrenia has a high diagnostic stability, according to previous works, prospective consistencies can vary from 52–100% 4549 . In our sample approximately 35% of the patients diagnosed with schizophrenia, presented a change in their diagnosis (prospective consistency of 65%).…”
Section: Discussionmentioning
confidence: 99%
“…The current study determined the DS for psychotic disorders to be 46.3%. Two other studies determined the DS of schizophrenia to be 74% and 67% [19]. In another study, patients with an initial episode of schizophrenic psychosis showed the greatest DS (93%) [4].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand in our study, bipolar disorder showed relatively higher prospective and retrospective consistency than other studies. Dramatic representation of manic episodes can facilitate its diagnosis compared to other psychiatric disorders ( Atwoli et al, 2012) .…”
Section: Discussionmentioning
confidence: 99%
“…The stability of diagnosis refers to consistency or difference between preliminary and follow up examination of patient and is used to determine response to treatment and to examine progression of disease ( Atwoli et al, 2012) .…”
Section: Introductionmentioning
confidence: 99%